COMPARISON OF COMPOSITE BULK FILL MICROLEAKAGE LEVEL AND INCREMENTAL BULK TECHNIQUE COMBINATION IN CLASS I CAVITY RESTORATION - Putu Ratna Kusumadewi Giri; I Gusti Ayu Fienna Novianthi Sidiartha; Sari Kusumadewi; Baiq Rengganis Dewi Rinjani (Fakultas Kedokteran Gigi Unjani, 2023)
Microleakage is the formation of gaps on the surface of the restoration, which several factors can cause. Restorative material was developed to reduce microleakage. Bulk-fill composite resins are made to accelerate the process of composite resins when restored. Bulk-fill allows clamping to be done at once with a thickness of 4 mm and undergoes minimal polymerization shrinkage. The study aims to determine the microleakage in bulk restoration techniques and combination with bulk incremental in class I preparations differences. This research is an experimental laboratory study using a post-only group design. Thirty-two samples of maxillary premolar teeth were divided into two groups, with sixteen samples for each group. In group 1, the samples were restored by bulk technique, and in group 2 were restored using a combination of bulk and incremental techniques. All samples were immersed in 0.2% blue methylene solution for 24 hours. Microleakage was measured using a 50x magnification stereomicroscope using a micrometer ruler in millimeter microscope units with an accuracy of 0.1 mm. The results showed that the microleakage value in the bulk technique was more significant than in the combination technique. Data were analyzed using univariate tests. The analysis showed significant differences between the two groups (p <0.05). This study concludes that the composite resin's restoration with a combination of bulk and incremental techniques produces smaller microleakage than the bulk technique. DOI : 10.54052/jhds.v3n1.p11-20